Adsorption isotherm analysis for CO2 capture using barium oxide impregnated iron (iii) oxide by ultrasonic-assisted synthesis - Lahuri, Azizul Hakim; Yarmo, Mohd Ambar; Abu Tahari, Maratun Najiha; Dzakaria, Norliza (Trans Tech Publications, 2022)
The barium oxide impregnated iron(III) oxide (BaO/Fe2O3) adsorbent was synthesized by an ultrasonic-assisted method. The adsorbent was calcined at 200-500 °C and its adsorption capacity was measured. The ultrasonic-assisted synthesis generated well-dispersed of BaO on Fe2O3 by giving none of the BaO peaks were observed through the XRD pattern. The most efficient adsorbent of BaO/Fe2O3200 was calcined at 200 °C with adsorption capacity for physisorption and chemisorption of 5.01 and 88.81 mg/g respectively. Besides other carbonate species, it was believed the presence of the hydroxyl group could enhance the sorption by forming bicarbonate upon CO2 chemisorption. It is also possessed a lower desorption range compared to BaO and Fe2O3 alone. The experimental CO2 adsorption isotherm at 25 °C fit better with the Freundlich isotherm model. It implies a favorable adsorption process with multilayer adsorption occurs onto the heterogeneous surface.